Chronic health effects associated with electronic cigarette use: A systematic review - Wasfi, Rania A.; Bang, Felix; de Groh, Margaret; Champagne, Andre; Han, Arum; Lang, Justin J.; McFaull, Steven R.; Melvin, Alexandria; Pipe, Andrew Lawrence; Saxena, Shika; Thompson, Wendy; Warner, Emily; et al. (Frontiers in Public Health, 2022)
Introduction: Over the last decade, e-cigarette use has been on the rise, with growing health concerns. The objective of this systematic review was to update findings for chronic health outcomes associated with e-cigarette use from the 2018 National Academies of Sciences, Engineering, and Medicine (NASEM) report. Methods: Three bibliographic databases were searched to identify studies comparing the chronic health effects of e-cigarette users (ECU) to non-smokers (NS), smokers and/or dual-users, indexed between August 31, 2017 and January 29, 2021. Two independent reviewers screened abstracts and full-texts. Data were extracted by one reviewer and verified by a second. Outcomes were narratively synthesized using counts, based on statistical significance and direction of association stratified by study design and exposure type. Risk of bias and certainty of evidence was assessed. The protocol was prospectively registered on Open Science Framework https://osf.io/u9btp. Results: A total of 180 papers were eligible, this review focused on 91 papers for the 11 most frequently reported outcomes, from which 59 reported on daily-ECU. The certainty of evidence for all outcomes was very low due to study design (84% cross-sectional) and exposure type (27% reported on exclusive e-cigarette use, i.e., never smoked traditional cigarettes). Overall, the summary of results for nearly all outcomes, including inflammation, immune response, periodontal and peri-implant clinical parameters, lung function, respiratory symptoms, and cardiovascular disease, suggested either non-significant or mixed results when daily-ECU was compared to NS. This was also observed when comparing exclusive-ECU to NS. The only notable exception was related to oral health where most (11/14) studies reported significantly higher inflammation among daily-ECU versus NS. Compared to smokers, exclusive-ECU had no statistically significant differences in inflammation or periodontal clinical parameters, but mixed findings for peri-implant clinical parameters. Conclusions: This review provides an update to the 2018 NASEM report on chronic health effects of e-cigarette use. While the number of studies has grown, the certainty of evidence remains very low, largely due to cross-sectional designs and a lack of reporting on exclusive e-cigarette exposure. There remains a need for higher quality intervention and prospective studies to assess causality, with a focus on exclusive e-cigarette use.